NephroCheck data compared to serum creatinine in various clinical settings. Issue 1 (December 2015) - Pajenda, Sahra; Ilhan-Mutlu, Aysegül; Preusser, Matthias; Roka, Sebastian; Druml, Wilfred; Wagner, Ludwig
Abstract Background Acute kidney injury is frequently observed at the intensive care unit, after surgery, and after toxic drug administration. A rise in serum creatinine and a fall in urine output are consequences of much earlier injury to the most sensitive part of tubular cells located at the proximal tubule. The aim of the present study was to investigate the course of two cell-cycle arrest urinary biomarkers compared to serum creatinine in four clinical settings: ischemic reperfusion injury, cardiac failure, severe acute kidney injury, and chemotherapy-induced kidney injury. Methods A recently developed bedside test known as NephroCheck measures two urinary parameters: insulin-like growth factor binding protein 7 (IGFBP7) and tissue inhibitor of metalloproteinase-2 (TIMP-2). The test is based on a sandwich immunoassay technique. The final test output, labeled AKIRisk, is shown as a numeric result. Results This report revealed that [IGFBP7] · [TIMP-2] in urine rise rapidly prior to any change in serum creatinine. A unique feature of all four clinical settings is that a rapid decline predicts the recovery of kidney function. Besides, a subclinical kidney injury might be detected by the test. Conclusion This bedside test detects biomarkers of renal injury. A rapid decline in AKIRisk was associated with the restoration of kidney function, whereas a prolonged high AKIRisk score was associated with end-stage renal disease. However, the dynamics seem to differ, depending on the cause and the extent of injury. Further studies will be needed to clarify the issue.